LITERASI MEDIA DIGITAL DI KOMUNITAS VIDEOGRAPHER âLINKPICTUREIDâ - Abdullah, Ahmad Zakki; Ayuningtyas, Fitria; Uljanatunnisa, Uljanatunnisa (Universitas Esa Unggul, 2018)
AbstractVarious phenomena due to digital media to form a very dynamic user behavior lately. In Indonesia, the legal basis of the ITE Law covers a very narrow and unclear discussion of which of the permissible and unauthorized signs are allowed. This situation is due to the gap between social development with the digital media in everyday life in society. References on the use of digital media is certainly very broad, such as the use for socializing, preaching, announcement, opinion sharing, association, discussion and so forth. In optimizing the use of media certainly needed a socialization and counseling